Teaching distance relay using Matlab/Simulink graphical user interface - Muhd Hafizi, Idris; Surya, Hardi; Mohd Zamri, Hasan (Elsevier Ltd., 2013)
Link to publisher's homepage at http://www.elsevier.com/